2012
DOI: 10.1021/jm3004009
|View full text |Cite
|
Sign up to set email alerts
|

Fluorocyclopentenyl-cytosine with Broad Spectrum and Potent Antitumor Activity

Abstract: On the basis of the potent biological activity of cyclopentenyl-pyrimidines, fluorocyclopentenyl-pyrimidines were designed and synthesized from D-ribose. Among these, the cytosine derivative 5a showed highly potent antigrowth effects in a broad range of tumor cell lines and very potent antitumor activity in a nude mouse tumor xenograft model implanted with A549 human lung cancer cells. However, its 2'-deoxycytidine derivative 5b did not show any antigrowth effects, indicating that 2'-hydroxyl group is essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…This explains the lack of cross resistance between gemcitabine and RX-3117 and will increase the potential of RX-3117 to be used against these tumors. Along with being active in gemcitabine resistant cell lines in vitro [3, 5], RX-3117 also showed in vivo activity against various tumor types, including gemcitabine resistant tumors [5, 6]. Additionally, this study also showed a relation between UCK2 expression and UCK activity as well as of UCK2 expression and RX-3117 sensitivity, which suggests that UCK2 expression may be used to select patients for their sensitivity to RX-3117.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…This explains the lack of cross resistance between gemcitabine and RX-3117 and will increase the potential of RX-3117 to be used against these tumors. Along with being active in gemcitabine resistant cell lines in vitro [3, 5], RX-3117 also showed in vivo activity against various tumor types, including gemcitabine resistant tumors [5, 6]. Additionally, this study also showed a relation between UCK2 expression and UCK activity as well as of UCK2 expression and RX-3117 sensitivity, which suggests that UCK2 expression may be used to select patients for their sensitivity to RX-3117.…”
Section: Discussionmentioning
confidence: 67%
“…A cytidine analog, fluorocyclopentenylcytosine (RX-3117) (Fig 1), has shown promise as an anti-cancer drug since it showed considerable anti-tumor activity in various xenograft models [5], including models resistant to gemcitabine [6]. The lack of cross resistance between these two drugs suggests a difference in mechanism of action or method by which they are metabolized in cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be easily explained by the irreversible inhi-bition of the enzyme caused by this molecule, unlike the neplanocin A, which presents a reversible mechanism [38]. Thus, based on that, their 6′-fluorinated analogs were obtained by Jeong et al (Figure 19) [39].…”
Section: Fluorine In Medicinal Chemistry: Some Fluorinated Carbocyclimentioning
confidence: 98%